Pengaruh Financial Distress dan Volatilitas Arus Kas terhadap Keputusan Hedging - 10090121130, Tiara Rosaliawati; Edi Sukarmanto (Bandung Conference Series: Accountancy, 2025)
Abstract. This research aims to determine the influence of Financial Distress and cash flow volatility on Hedging decisions. In collecting data, researchers used a purposive sampling method to obtain data in accordance with predetermined criteria. The sample used in this research was 119 manufacturing companies with an observation period from 2019-2023, resulting in 595 observations. The research method used is a verification method with a quantitative approach. Hypothesis testing was carried out using multiple linear regression analysis using the Eviews test tool. The research results show that Financial Distress has a significant positive effect on Hedging decisions. Cash flow volatility has a significant influence in a positive direction on Hedging decisions. Future research is expected to use other measures or add other variables such as company size, leverage, capital structure, growth opportunity. Abstrak. Penelitian ini bertujuan untuk mengetahui pengaruh Financial Distress dan volatilitas arus kas mempengaruhi keputusan Hedging. Dalam pengambilan data, peneliti menggunakan metode purposive sampling sehingga mendapatkan data sesuai dengan kriteria yang telah ditetapkan. Sampel yang digunakan dalam penelitian ini sebanyak 119 perusahaan manufaktur dengan masa pengamatan dari tahun 2019-2023 sehingga diperoleh 595 pengamatan. Metode penelitian yang digunakan adalah metode verifikatif dengan pendekatan kuantitatif. Pengujian hipotesis dilakukan dengan menggunakan analisis regresi linear berganda dengan menggunakan alat uji Eviews. Dari hasil penelitian menunjukan bahwa Financial Distress berpengaruh signifikan dengan arah positif terhadap keputusan Hedging. Volatilitas arus kas erpengaruh signifikan dengan arah positif terhadap keputusan Hedging terhaap keputusan Hedging. Penelitian selanjutnya diharapkan menggunakan pengukur lain atau menambah variabel lain seperti ukuran Perusahaan, leverage, Struktur modal, growth opportunity.